2017
DOI: 10.1177/1521025117690159
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Learning Support Services in University Students’ Educational Outcomes

Abstract: Learning Support Services at the University of California, Santa Cruz is intended to aid students—particularly those who are at highest risk of academic failure—to master the required material and succeed in their courses. It includes two primary components: modified supplemental instruction (MSI) and tutoring. This study uses data from administrative records kept by University of California, Santa Cruz on its students’ academic experiences in the 2010–2011 to 2013–2014 academic years to examine the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Malm et al [10] have reported that a higher percent of students who used SI passed first-year engineering courses and had higher grades compared to students who did not use SI. Another study found that students who used SI gained 0.02 grade points for each additional SI session attended [11]. SI attendance has been demonstrated to have a positive effect on student performance, regardless of a student's past academic performance [10].…”
Section: Effect Of Si On Retention and Successmentioning
confidence: 99%
“…Malm et al [10] have reported that a higher percent of students who used SI passed first-year engineering courses and had higher grades compared to students who did not use SI. Another study found that students who used SI gained 0.02 grade points for each additional SI session attended [11]. SI attendance has been demonstrated to have a positive effect on student performance, regardless of a student's past academic performance [10].…”
Section: Effect Of Si On Retention and Successmentioning
confidence: 99%
“…Social support plays a crucial role in students and their learning outcomes at school (Balzer Carr & London, 2019). Gao and colleagues studied the role of support with students in China and affirmed that the students who receive support from friends, teachers, and family have higher achievement at school than the others (Gao et al, 2021).…”
Section: Social Support Helps Students Cope With Challenges and Difficultiesmentioning
confidence: 99%
“…Lack of social support can result in the student's not coping, procrastination, and dropping out of education. Social support includes emotional validation as well as practical support (Ertel et al, 2009;Balzer Carr & London, 2019;Runions et al, 2021).…”
Section: Social Support Helps Students Cope With Challenges and Difficultiesmentioning
confidence: 99%
“…Academic interventions that have been shown to increase student retention include: supplemental instruction and tutoring (Balzer Carr & London, 2019;Laskey & Hetzel, 2011), first-year seminar (Dalton & Crosby, 2014;Padgett & Keup, 2011), academic advising (Swecker et al, 2013;Zhang et al, 2017), student coaching (Capstick et al, 2019;Dalton & Crosby, 2014), and peer mentoring (Kiyama & Luca, 2014;Reyes, 2011). Glenn (2003) suggested that most effective interventions aimed at increasing the retention of Black students is to identify students with risk factors at enrollment and track their academic progress.…”
Section: Relevant Literaturementioning
confidence: 99%